Penerapan Model Pembelajaran PBL pada Materi Persamaan Kuadrat Berbantuan Komik untuk Meningkatkan Hasil Belajar Matematika - Peni, Maria Ermelinda; Samo, Damianus Dao; Madu, Aleksius (Griya Journal of Mathematics Education and Application, 2024)
This research was motivated by the low mathematics learning outcomes of class IX students at SMP Negeri 20 Kupang on Quadratic Equations material. The aim of this research is to improve the mathematics learning outcomes of class IX students at SMP Negeri 20 Kupang by applying the problem based learning model assisted by comic media (pixton) to the quadratic equation material.The research method used is Classroom Action Research Kemmis and Mc Taggart models which are carried out in 2 cycles with each cycle having 4 stages, namely: 1) planning; 2) implementation; 3) observation; and 4) reflection. The data collection techniques in this research are observation, tests and documentation, while the data analysis is descriptive qualitative and quantitative. The results of this research show that the percentage of classical student learning completeness in cycle I was 63.63%, increasing to 81.81% in cycle II, the value of implementing observations of teacher teaching activities in cycle I was 95%, increasing to 100% in cycle II and the value The implementation of student activities in cycle I was 85.71%, increasing to 100% in cycle II. Thus, it can be concluded that the application of the problem based learning model assisted by comics (pixton) can improve the learning outcomes of class IX students at SMP Negeri 20 Kupang in the quadratic equation material.